Stereolithography-based additive manufacturing of polymer-derived SiOC/SiC ceramic composites. Issue 13 (October 2022) - Essmeister, Johannes; Altun, Altan Alpay; Staudacher, Maximilian; Lube, Tanja; Schwentenwein, Martin; Konegger, Thomas
Abstract: In order to overcome challenges typically encountered during additive manufacturing of ceramics via the polymer precursor route, a novel polymer-derived SiOC/SiC composite system suitable for advanced geometric designs achievable by lithography-based ceramic manufacturing was established. The photoreactive resin system filled with 20 wt% SiC exhibits suitable viscosity characteristics, adequate stability against sedimentation, and a fast photocuring behavior. After printing and pyrolytic conversion, SiC particulates were well-dispersed within the polymer-derived SiOC matrix. A direct comparison with the unfilled polysiloxane-based resin system showed that the addition of particulate SiC increases handleability, reduces shrinkage, and significantly increases critical wall thicknesses up to 5 mm. The biaxial Ball-on-Three-Balls testing methodology yielded a characteristic strength of 325 MPa for SiOC/SiC composites. The results highlight the high potential of particle-filled preceramic polymer systems toward the fabrication of high-performance SiC-based materials by lithography-based additive manufacturing.